2015
DOI: 10.1016/j.urolonc.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Clostridium difficile infection after radical cystectomy for bladder cancer: Analysis of a contemporary series

Abstract: Introduction: This study seeks to evaluate the incidence and associated risk factors for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
(39 reference statements)
1
15
1
Order By: Relevance
“…It has been demonstrated that the development of CDI after cystectomy is associated with a 2.5-fold increase in mortality and adds approximately $22,634 in cost per hospitalization per patient 17 . Our institution's CDI incidence from 2010 to 2013 was closer to the high end of this range as reported in 2015 19 . The incidence of asymptomatic CD carriage is unfortunately unknown in cystectomy patients.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…It has been demonstrated that the development of CDI after cystectomy is associated with a 2.5-fold increase in mortality and adds approximately $22,634 in cost per hospitalization per patient 17 . Our institution's CDI incidence from 2010 to 2013 was closer to the high end of this range as reported in 2015 19 . The incidence of asymptomatic CD carriage is unfortunately unknown in cystectomy patients.…”
Section: Introductionsupporting
confidence: 78%
“…CDI rates on other floors, including medical and colorectal surgical wards, demonstrated a less pronounced rate of CDI reduction ranging from 5 to 33%. The generalizability of our results may be limited due to the higher incidence rate of CDI compared to other institutions [16][17][18][19] . However, CDI rates are rising and recent reports suggest that CDI rates in cystectomy patients may be even higher at other institutions 5,20 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
See 1 more Smart Citation
“…[7,9,2931] Although RC is a risk factor for CDAD in various urological surgeries, [32] our results show a relatively high incidence of CDAD. However, some investigations examined the trends toward higher incidence rates of C difficile infection in studies with medical record review [30,31] than in studies using claim data or nationwide sample data, [9,29] which have a probable reporting bias. Our results regarding the incidence of C difficile infection were comparable to those of previous studies that directly reviewed the medical records of patients with RC.…”
Section: Discussionmentioning
confidence: 76%
“…Inappropriate use of antibiotics may cause a variety of adverse effects, including serious complications such as allergic reactions, organ dysfunction, or Clostridioides difficile infection [34][35][36][37][38][39]. Perhaps most concerning is that self-medication infers self-diagnosis, significantly increasing the risk for delayed, masked, or missed diagnoses [40].…”
Section: Plos Onementioning
confidence: 99%